2019
DOI: 10.1039/c9qo00892f
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of manganese dioxide nanoparticles on modified poly 2,4-dichlorostyrene microspheres: a highly efficient and recyclable catalyst for borrowing hydrogen reactions

Abstract: Modified poly 2,4-dichlorostyrene microspheres were designed and synthesized, and were proved to be an effective carrier to synthesize supported manganese dioxide nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 101 publications
0
29
0
Order By: Relevance
“…Among these elements, manganese is the main topic of numerous publications devoted to tandem oxidation, mainly Mn(III) and Mn(IV) . For instance, manganese has recently attracted wide interest for multicomponent reactions based on pincer‐type manganese complexes …”
Section: Reactivity Of Eco‐mn Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these elements, manganese is the main topic of numerous publications devoted to tandem oxidation, mainly Mn(III) and Mn(IV) . For instance, manganese has recently attracted wide interest for multicomponent reactions based on pincer‐type manganese complexes …”
Section: Reactivity Of Eco‐mn Catalystsmentioning
confidence: 99%
“…[95][96][97][98] For instance, manganese has recently attracted wide interest for multicomponent reactions based on pincer-type manganese complexes. [99][100][101][102][103][104][105][106] Eco-Mn LA and Eco-Mn Ox catalysts possess a polymetallic composition which combines metal transition elements with Lewis or Brønsted acidity properties (Mn, Fe, Al) and oxidative properties (Mn, Fe). Eco-Mn LA and Eco-Mn Ox catalysts were studied in sequential tandem oxidation as a "Janus catalyst", which is an eco-material with two different but concomitant catalytic properties.…”
Section: Tandem Sequential Oxidation Catalyzed By Eco-mn La Andmentioning
confidence: 99%
“…After a series of experiments, it was found that Ag@MnO 2 revealed catalytic activity in toluene (entry 8), with only small amount of the target product, N-benzylaniline (3a) produced in solvents such as EtOAc, DCM, and MeOH ( Table 1, entries 1-7), which indicates that there may be a similar solvent effect to our previous work. 37,38 Besides, compared to room temperature and 60 °C, it was observed that this reaction produced a higher yield at 110 °C (Table 1, entries 8 and 9). This result may disclose that it has a slightly higher energy barrier.…”
Section: Characterization Of the Ag@mno 2 Nanorodmentioning
confidence: 93%
“…In addition, Ag nano particles have been shown to have outstanding ability as catalyst in many organic reactions. [30][31][32][33] Based on our recent discoveries on hydrogen-borrowing reactions [34][35][36][37][38] and the properties of manganese oxides (MnO 2 ) nanorods and Ag nanoparticles, we herein report the synthesis and application of Silver/manganese dioxide (Ag@MnO 2 ) nanorods as a catalyst, which has higher catalytic activity after several cycles and which is much cheaper than other catalysts. The Ag@MnO 2 nanorods are characterized by several physical techniques.…”
Section: Introductionmentioning
confidence: 99%
“…They can be achieved by the combination of components of diverse origin, for instance, organic and inorganic moieties. [10][11][12][13][14] It is worth noting that this methodology requires a detailed and comprehensive search for the mentioned components.…”
Section: Introductionmentioning
confidence: 99%